Getting There: Exploring the Role of Expectations and Preproduction Delays in Processes of Organizational Founding - Lomi, Alessandro; Larsen, Erik R.; Wezel, Filippo Carlo (Organization Science, 2010)
Because of preproduction delays, environmental conditions at founding cannot explain organization-building decisions taken earlier. As a consequence, environmental conditions at founding cannot explain organizational founding. Future levels of resource availability may be estimated, but not directly observed by potential entrepreneurs at the time at which they decide to enter preproduction. In this paper, we take these considerations as our starting point to build a dynamic feedback model of organization founding. According to the model, organizational founding is driven by expectations that entrepreneurs form about future levels of resources and, only indirectly, by current levels of population density. We explore the behavior of the model under a variety of experimental conditions. We show that the qualitative behavior of the model is consistent with studies that have linked the duration of preproduction stage with fluctuations in density during population maturity. Our simulation analyses sustains three main conclusions. First, historical trajectories of organizational populations that are consistent with empirical observations may be produced by mechanisms that are not directly dependent on density. Second, alternative hypotheses about how expectations are formed produce qualitatively different historical trajectories of density. Third, fluctuations in numbers of organizations are linked to specific aspects of individual organization-building decisions.